Sound and safe: The role of leader motivating language and follower self-leadership in feelings of psychological safety - Milton Mayfield; Jacqueline Mayfield (Administrative Sciences, 2021)
This manuscript presents a study on how leader motivating language and follower self-leadership act to influence a follower's feelings of psychological safety. This study found that both constructs significantly influenced psychological safety in samples from India and the USA. Additionally, this study found that this influence occurred through the mediating processes of trust in leadership, leader inclusiveness, and role clarity. These mediators fully explained motivating language's relationship with psychological safety, but only partially explained self-leadership's relationship. Differences existed in the model between samples, but self-leadership showed an overall consistency between the samples for most relationships. Follow-up analysis indicated that self-leadership without leader communication support lead to a weak or non-existent relationship between self-leadership and psychological safety, but a positive and relatively strong relationship in the presence of motivating language.
Keywords: 350; communication; leadership; motivating language; psychological safety; self-leadership